Rola zarządzania procesami biznesowymi w architekturze zorientowanej na usługi - Nowicki, Adam; Nosal, Mariusz; Wydmuch, Gracja (Enterprise Process Orientation in SOA Approach, 2007)
This paper presents the place and the role of Business Process Management in Service-Oriented Architecture approach. The flexibility of information services in the current enterprise needs states of a nature SOA issue. The BPM has got a new position in the life-cycle of business service. The authors of this paper discuss the relationships between both conceptions and their reaction to each other.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Informatyka Ekonomiczna (11); 2007; nr 1156, s. 181-192